Musicoterapia nas dificuldades do processamento auditivo - Kurrle, Marcia de Mattos (2004)
Being known that there are children who complain about having hearing processes disorders, this research intends to verify the influence of the musictherapy as a therapeutic resource in the performance of the hearing skills in the hearing process, and complainments during their school learning. The sample was composed by ten (10) students from first to third grade of the basic level, from four (4) schools from Santa Maria RS, two of the schools were public and the other two private. It was given to the teachers a pool, with questions that refered to he learning difficulties of the patients involved. They went through the peripheral hearing test and central hearing test. Among those who showed up alteration in the hearing process, a group chosen at random was exposed to musictherapy. After fifteen (15) musictherapeutic session, the group had to go through the same tests that had been made previously. Concerning the performance of the hearing skills, were obtained, as result, a statistically significant improvement in all the patients, and, in this way, it was possible to conclude that musictherapy had a positive influence in the skills of hearing processament of the studied group.